A quality improvement project to standardize chaplain documentation in the electronic medical record. Issue 2 (3rd April 2022) - Stewart, Nicholas S.; Henley, Joanne L. S.; Smith, Leah S.; Garvin, Jonna R.
Abstract: Medical record documentation by hospital chaplains is an under-researched and under-published field. Because documentation serves both as a register of chaplain interventions and as a collaborative tool for interdisciplinary communication, it should be written in a way that is clear, concise, and consistent. As chaplains continue to integrate with other medical professions in interdisciplinary care, careful attention should be given to the way in which communication of the chaplain role, functioning, and patient information obtained is conveyed. This quality improvement project standardized chaplain documentation in one health system of 15 medical centers, provides insights and resources devised from the project, and offers considerations for other systems contemplating future changes toward standardizing documentation.